A Biobehavioral Perspective on Telomere Length and the Exposome. (October 2014) - Lyon, Debra E.; Starkweather, Angela R.; Montpetit, Alison; Menzies, Victoria; Jallo, Nancy
A major objective of biobehavioral research is defining the mechanisms that underlie linkages among behavior, biology, health, and disease. The genomic revolution has demonstrated the importance of studying the role of the environment in (epi)genetic mechanisms. The idea that interactions between environment and genetics influence health outcomes is a central concept of the exposome, a measure of environmental exposures throughout a lifetime. Research suggests that telomere length (TL) and biologic factors involved in telomere stability may provide an understanding of the effects of gene–environment interaction on disease risk. Telomeres, thus, have become important biomarkers for aging as well as for stress-related disease. However, incorporating telomeres into biobehavioral research requires consideration of several aspects of the exposome. Internal and external modifiable and nonmodifiable exposures have the potential to influence TL. Future research utilizing the concept of the exposome will provide meaningful findings related to exposure sources as well as dosage and duration across the life span that influence telomere biology and disease occurrence. Such findings can be translated into clinical practice and may provide a basis for personalized disease prevention and treatment approaches.